1996
DOI: 10.1111/j.1476-5381.1996.tb15541.x
|View full text |Cite
|
Sign up to set email alerts
|

Dual regulation of the Na+/H+‐exchange in rat peritoneal mast cells: role of protein kinase C and calcium on pHi regulation and histamine release

Abstract: 1 The purpose of this study was to compare the actions of phorbol 12-myristate 13-acetate (PMA) and ionomycin on Na+/H+ exchange activation and histamine release to that of compound 48/80 in order to study the possible relationship between pHi and secretion of histamine in rat peritoneal mast cells.2 Resting pHi in mast cells suspended in a bicarbonate-free physiological salt solution amounted to 6.73 + 0.05 (mean + s.d., n = 52). 3 PMA (20 nM) induced a substantial but rather slow increase in pHi. This respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…The inhibition of Na + /K + -ATPase may induce an inhibition on the activity of the Na + /H + exchanger [13]. On the other hand, the activation of PKC in rat mast cells results in an increase in the Na + /H + -antiporter activity [3,12]. This same effect was also described in lymphocytes and platelets [14,15].…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…The inhibition of Na + /K + -ATPase may induce an inhibition on the activity of the Na + /H + exchanger [13]. On the other hand, the activation of PKC in rat mast cells results in an increase in the Na + /H + -antiporter activity [3,12]. This same effect was also described in lymphocytes and platelets [14,15].…”
Section: Introductionsupporting
confidence: 53%
“…The activity of the Na + /H + antiporter is modulated by different phosphorylation pathways [3,7,10,12]. The phorbol esther PMA, a PKC activator, is known to increase the velocity of the Na + /H + transporter [12,39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the precise mode of action of compound 48/80 is unknown it has become evident that both the mobilization and the influx of Ca 2þ and the activation of PKC are required for manifest exocytosis, i.e., the release of histamine from the granules into the extracellular environment [4]. To which extent eicosanoids play a role in the degranulation process is not clear, but it cannot be excluded that these substances support the signal transduction process.…”
Section: Introductionmentioning
confidence: 98%
“…Thus far, only chloride channels [4,5] and two electrolyte transporters have been studied in mast cells, one is the Na + /K + -adenosine triphosphatase (ATPase) [6] and the other the Na + /H + exchanger [7][8][9]. The aspects of a possible relationship between calcium and sodium in the mast cell response have been studied by a few authors [10][11][12][13], and we have previously reported that in rat mast cells, there is an active Na + /H + exchanger [7] and no sodium channels [14].…”
Section: Introductionmentioning
confidence: 99%